A rare case report of acute acalculous cholecystitis in active chronic hepatitis C virus infection - Widiani, Putu Indri; Santosa, Nyoman Angga; WIrawan, I. Made Suma (International Journal of Advances in Medicine, 2022)
Acute acalculous cholecystitis (AAC) is an inflammation of gallbladder with absence of gall stones or bile sludge. Daily cases reported about 90-95% of the acute cholecystitis present with gall stone, while only 5-15% occur without gall stones obstruction. AAC is reported associated with Epstein bar virus infection, hepatitis B virus and hepatitis A virus. Hepatitis C-induced AAC cases still rare. This case report presents a 49-years-old female patient with epigastric pain, nausea, yellowish sclera, tea urine color, pale stool and there was a history of the patient's husband with hepatitis C. On physical examination there was epigastric and right hypochondriac pain, and positive murphy sign. There was leukocytosis, hyperbilirubinemia and an increase in SGPT (1.360 U/L) and SGOT (1.720 U/L). Antibodies to HCV were positive. Abdominal ultrasonography showed cholecystitis with no biliary duct dilatation and no parenchymal liver disease appearance The patient was diagnosed with acute chronic hepatitis C and cholecystitis. Pathophysiology of hepatitis C induced AAC is not fully understood, but is thought to be due to complexes immune, directly infect gallbladder and proximal biliary epithelial cells uncontrolled, increased portal/septal myofibroblasts activity and inflammation. The presence of AAC with an increase in serum levels of SGOT and SGPT 5-10 times the normal limit should be suspected due to acute hepatitis viral infection. Further research still needs to be done to determine the relationship between hepatitis C and the incidence of AAC.